Eksaminasi Putusan Pengadilan Negeri Tentang Penjatuhan Sanksi Pidana Pada Perkara Tindak Pidana Korupsi Sepanjang Tahun 2018: Bahasa Indonesia - July Wiarti; Aprinda Dika Pratama (UIR Press, 2019)
The results of criminal case decisions greatly affect the eradication of the relevant criminal offenses. So it is necessary to examine these decisions to see whether or not such judges' decisions can eradicate corruption or not. Moreover, it is understood that one of the purposes of criminal giving is a deterrent effect for both the perpetrators and others. Therefore the focus of this study: first, What is the form of criminal sanctions imposed by the Judge of the Pekanbaru District Court on Corruption Cases during 2018; second, how the imposition of criminal sanctions by the Pekanbaru District Court Judge in the Corruption Case in 2018 is related to the eradication of corruption. This type of research is a normative legal research that is based on mere secondary data and supplemented with interviews with certain parties. The research results obtained are the form of criminal sanctions given by judges in cases of corruption in the Pekanbaru District Court is only in the range of one to four years, twenty cases and for five years to ten years there are three remaining cases are cases that the prosecution does not can be accepted and the defendant is released from punishment. The sentence given by the judge on corruption cases in the Pekanbaru district court is still far from being said to have an impact on the eradication of corruption itself. Because, from the form of the sentence alone there are still many light and only given a special minimum sentence. Even though the losses suffered by the State are quite large. Then, many cases are subject to Article 3 of Article 2, where the sentence is lighter than Article 2